THE INFLUENCE OF CREATIVITY, BUSINESS FUNDING, AND GENDER EQUALITY ON THE PERFORMANCE OF WOMEN ENTREPRENEURS’SMALL MICRO MEDIUM ENTERPRISES - Suprani, Yun; Khoiron, M. (Jurnal Aplikasi Manajemen, 2018)
This researchis to comparewomen entrepreneurs UMKM in Palembang and K Ogan Ilir Regency and analyzed by using the 17 SPSS. The similarities of women'screativities in managing UMKM in Palembang and Ogan Ilir Regency were not optimized. Theyjust try to continue the family's business that has existed before. Herein, all the product design or packaging still uses the existing ones. Therefore, they generally rely on the family'sfunding or personal savings. They are afraid of borrowing business funding from banks, some of them even do not know how to apply for bank loans. Meanwhile, the differences between women entrepreneurs in managing UMKM between in Palembang and Ogan Ilir Regencycould be seen from the gender equality.Women were more autonomous to manage the UMKM in Ogan Ilir Regency. The next researcher is expected to examine more respondents dan wider research area, and this research is expected to give contribution and references to related institutions.